The Impact of Supply Chain Digitalization on Enterprises' Foreign Trade - Li, Linyue; Pan, Ran (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Examining the influence of supply chain digital construction upon enterprise export trade furnishes empirical substantiation for Chinese firms' global expansion. This analysis dissects the mechanism underpinning supply chain digitalization across three vectors: synergistic interplay, capital expenditure mitigation, and Information transparency. It further probes heterogeneous manifestations contingent on external contingencies, encompassing enterprise market standing and pollution categorization. Findings reveal that supply chain digitalization markedly propels enterprise foreign commerce development, principally via synergies, capital cost amelioration, and Information transparency enhancements. External environmental constituents, notably digital backbone frameworks and market fragmentation extent, moderate this impact on export trade. Consequent deductions necessitate Chinese enterprises expediting supply chain digitalization, harnessing digital modalities to augment supply chain collaborative proficiency and reactivity, curtail capital outlays, and elevate informational lucidity, thereby bolstering international market standing. Concurrently, policymakers must enact supportive statutes facilitating enterprise digital metamorphosis within supply chains. Additionally, refining the external milieu—fortifying digital infrastructure and diminishing market segmentation—proves indispensable for unleashing the complete affirmative function of supply chain digitalization in enterprise export trade.